Application of purchasing power parity indices for studying inflation processes in Ukraine - Маляр, Л. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
This article focuses on the problem of applying the Big Mac index as a meaningful indicator that characterizes the state of the economy as a whole, as well as on determining the relationship between such economic indicators as exchange rate, inflation index and money supply (the NBU aggregate М3) in Ukraine. The sample of the countries was analyzed and the countries with the highest and lowest value of “Big Mac” were determined. Moreover, there is a possibility of using the “Big Mac” index as a measure of undervaluation or overvaluation of the currency, conclusions for specific countries were made. The clustering method is applied, which allows selecting clusters and constructing a Kohonen’s network. For the clustering procedure the following sample of countries and factors was drawn: GDP, annual inflation and the value of the “Big Mac”. As a result, three clusters were formed and the key factor for their formation was GDP. In addition, clusters differ in the level of annual inflation and the value of the “Big Mac”. There was determined a relationship between the value of the “Big Mac”, the exchange rate, the inflation index and aggregate M3of the NBU in Ukraine. A correlation analysis was conducted and corresponding trend lines characterized by regression equation and high coefficient of determination were selected. A multiple linear model reflecting simultaneously the dependence of the value of the “Big Mac” on the exchange rate, the inflation index and the money supply was built. Verification of the model by the criteria of relevance and adequacy showed its quality and possibility of applying it to forecasting. The dynamics of the Ukrainian “borscht” index which can be considered similar to the “Big Mac” index was considered. A time-series of these indices were compared and their dynamics was analyzed.